Touching the earth and the sky - Boelen, Jan; Delrue, Ronny (Leuven Acco, 2009)
The research project 'Touching the earth and the sky' involved several episodes. The whole process started with three working periods - each period consisting of three months - at the .ekwc (European Ceramic Workcentre) in 's-Hertogenbosch. During the first period (in 2004), the aspect of the oeuvre concerning content (mental and environmental pollution) was completed and deepened by a specific medium: the construction of a CCM-laboratory (Centre for Cloning and Manipulation).In the second period (in 2005), the Mind scultpures originated. The third period (in 2007) involved a combined residency in cooperation with two architects: Stéphane Beel and Wim Goes. The study aimed at the realisation of two Mind Sculptures as main building. This notion contained the basic principle of the film 'Touching te eartch and the sky', which was created at the FLACC, the studio for plastic arts in Gent. In addition, Ronny Delrue's doctoral project, named 'The controlled uncontrollability in the process of drawing', started in 2004 and had its influence on the project. The drawings illustrate the registration of the mind. They are a sort of breeding ground, out of which new images originate. Moreover, they witness the "non-genesis": for some reason the piece of art is not realised or even is destroyed. The entire study resulted in the exhibition 'Touching the earth and sky' in Z33, consisting of one installation, a Mind Scultpure.